Promoting community food security learning: a case study of Ban Pa Yang, Moo 4, Tha Ngio Sub-district, Mueang District, Nakhon Si Thammarat Province, Thailand - Daycho Khaenamkhaew (Cogent Social Sciences, 2024)
This study aims to study: 1) The level of food security in the community, 2) The promotion of food security learning in the community, and using a mixed-methods approach by conducting quantitative and qualitative research. For quantitative research, a questionnaire-based survey was conducted on 309 households. Data were analyzed to determine frequency, percentage, mean, and standard deviation. For the qualitative research, an interview form and an observation record form were used. Interviews and observations with key informants were conducted, selecting 10 households. The data were analyzed, summarized, and presented through a qualitative analysis. The findings of the study were as follows: 1) The level of food security in the community in all aspects was high. 2) The promotion of food security learning in the community focus on diverse, safe, and mindful eating at the individual level while ensuring economic means for healthy food. At the household level, emphasis is placed on nutritional knowledge, efficient meal planning using local ingredients, and budgeting to maintain health without financial stress. Community-level principles advocate sustainable agriculture, local food consumption, and resource sharing to enhance access to nutritious food. These strategies aim to bolster educational efforts, agricultural development, preservation of local food traditions, promotion of food tourism, and support for local markets.